A European student perspective of international internship value. (3rd April 2023) - Zhong, YunYing (Susan); Murphy, Kevin; Khalilzadeh, Jalayer; Smith, Riana Madison; Weinland, Jeffrey
ABSTRACT: Despite the European Union's current interest in promoting global skill development for hospitality and tourism professionals, international internships for European students remains an under-investigated topic. This study applied the concept of "value" from marketing literature to understand hospitality and tourism students' satisfaction and loyalty intention of international internship programs at two European universities. Value was conceptualized as a trade-off between what students "give" and "get" from their programs. Perceived value was proposed to positively affect students' satisfaction and loyalty intention. The proposed model was estimated using Partial Least Square (PLS) path modeling. The findings suggested that European students' value perception was crucial in forming satisfaction and loyalty intentions. Although students' value perception was significantly affected by both their "get" and "give" assessments, benefits exerted more weight on overall value evaluation than sacrifices. The study results provided meaningful practical and theoretical implications for hospitality internship research.